(untitled) (World Science, 2023)
The research deals with the study of communicative strategies and tactics in medical collegial discourse. The speech strategies of communicators have been studied based on audio recordings of dialogues between students/doctors and patients, and typical macro intentions of student-doctors ("support", "prohibition", "ignoring") were identified, according to this was suggested the classification of communication strategies and tactics: cognitive reframing, persuasive Communication strategy, motivational interviewing techniques, feedback tactics, information strategy. The analysis showed that the appropriateness of the selected approach depends on the context of the situation and affects the achievement of mutual understanding with the patient. The problem of studying communicative strategies and tactics of professional discourse is widely presented in the research of foreign authors such as J. Heritage, D.W. Maynard, S. Fleischman, N. Ainsworth-Vaughn, et al. Communication between a doctor and a patient is at the center of researchers’ attention as a phenomenon that acts as a multifaceted construct and is considered in modern linguistics from pragmalinguistic, dialogic, culturological, and sociolinguistic positions. Reforms carried out in the healthcare system over the past years have led to the need to change the paradigm of doctor-patient communicative interaction models: the paternalistic model is replaced by a collegial model, which has led to the analysis of the effectiveness of the doctor-patient communication models, the study of the specifics of the linguistic implementation of their cognitive and speech strategies, comparing the results obtained and determining the reasons for the success or failure of specific speech strategies and tactics.